Perbandingan Metode Demonstrasi dan Video Terhadap Keterampilan Perawatan Payudara Ibu Hamil Trimester III - Hamidiyanti, Baiq Yuni Fitri; Pratiwi, Intan Gumilang; Sulianty, Ati; Suseno, Mutiara Rachmawati; Faiqah, Syajaratuddur (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Exclusive breastfeeding given to children from birth to 6 months of age with no supplementary foods and beverages. exclusive breastfeeding was one of the keys to reduce infant mortality rate (IMR). The coverage of babies receiving exclusive breast milk in 2019 was 67.74%. The low level of exclusive breastfeeding is influenced by many factors, one of which is the mother's lack of awareness of the importance of breastfeeding in the first 6 months after giving birth. Breasts need to be prepared during pregnancy, which impacts providing IMD (Early Initiation of Breastfeeding), which influences exclusive breastfeeding. Research aim was to compare the effectiveness between Â media phantom and video regarding the Breast Care Skills of Pregnant Women in the Third Trimester. The research used quasi-experiment with a non-equivalent control group design. The research sample was obtained by purposive sampling of 60 people (30 intervention groups and 30 control groups). The results of data analysis used Mann-Whitney test. Results showed that p value p = 0.000, meaning p < 0.05, stating that the demonstration using phantom media was more effective in improving breast care skills in third-trimester pregnant women. In conclusion, it is hoped that this guide can be used by stakeholders or service partners and motivate pregnant women to carry out breast care since pregnancy so that they can successfully provide exclusive breastfeeding until the baby reaches 6 months.